From Texas With Love - Gutman, Dan (New York: HarperCollins publishers, 2014)
The wackiest road trip in history continues as the McDonald twins travel the Southwest dodging nefarious villains and visiting weird but true American landmarks"-- Provided by publisher
New York Times Bestselling Author
Ages 8-12
Keywords: Action and adventure fiction; Children's Stepfamilies Books; Children's Siblings Books; Children's Action & Adventure Books -- New York